Consumer Sensory Evaluation of Ground Beef and Plant-Based Ground Beef Alternatives Used in a Hamburger Application - L. A. Egger; K. J. Farmer; E. S. Beyer; K. R. Lybarger; J. L. Vipham; M. D. Zumbaugh; M. D. Chao; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2023)
Objective:The objective of this study was to evaluate the palatability traits and consumer acceptance of three plant-based ground beef alternatives in comparison to ground beef in a foodservice-like hamburger application. Study Description:Three popular plant-based ground beef alternatives (GBA) and 80% lean, 20% fat composition ground beef chubs (n = 20) were selected for consumer analysis. Samples were cooked to an internal temperature of 160°F, plated on a bun and served to consumers with the opportunity to apply ketchup, mustard, cheese, lettuce, and pickles. Consumers evaluated the differences in palatability traits and purchase intent for the samples identified as: Ground Beef, Foodservice GBA, Retail GBA, and Traditional GBA. The Bottom Line:This research indicates the use of ground beef and ground beef alternatives provide different eating experiences when consumed as a complete hamburger and should be marketed as such by the foodservice and retail sectors.
Keywords: ground beef; ground beef alternatives; plant-based